Correlation between cough and gastroesophageal reflux in children - A. V. Burlutskaya; A. V. Statova; O. G. Korobkina; Yu. V. Pisotskaya; D. V. Ustyuzhaninа (Инновационная медицина Кубани, 2022)
For many decades, the scientific community of medical professionals has wondered if there is a correlation between cough and gastroesophageal reflux. This problem is relevant for doctors of various specialties. The importance of this issue is due to practical application since it determines the tactics of diagnosis and treatment both for cough and gastroesophageal reflux. The article provides an analysis of Russian and foreign literature data, based on which we can conclude that there is a correlation between gastroesophageal reflux (gastroesophageal reflux disease) and cough.